Vibration control beam using piezoelectric-based smart materials. (May 2015) - Kerboua, M.; Megnounif, A.; Benguediab, M.; Benrahou, K.H.; Kaoulala, F.
Abstract: Traditionally, the vibrations of bituminous beam are damped by inherent damping properties. In this research, smart materials are used to control and reduce the vibration of such beams. The study focused on the passive piezoelectric vibration shunt control technique. Firstly, the finite element method was used in order to determine optimal design and location of piezoelectric transducers. Based on the results obtained from a simple Euler Bernoulli beam evaluation, up to 42% of bending vibration reduction was gained by using smart beam. Secondly, the analytical study of passive piezoelectric vibration shunt control of cantilever beam was undertaken. The equation of motion of a composite beam (cantilever beam bonded with a PZT patch) using Hamilton's principle and Galerkin's method has been derived.